Perception of people undergoing kidney transplantation about organ donation - Santos, Bianca Pozza dos; Viegas, Aline da Costa; Paula, Elaine Amaral de; Lise, Fernanda; Rodrigues, Luiza Pereira Vargas; Fuculo Júnior, Paulo Roberto Boeira; Schwartz, Eda (ABCS Health Sciences, 2018)
Introduction: Chronic kidney disease has high prevalence and morbidity/mortality in the Brazil and in the world, being responsible for social, economic and quality of life losses. Among the modalities of renal substitutive therapy, the transplantation is considered the best treatment because it presents lower cost, provides higher quality of life and increased survival. However, the realization of a transplant is possible only from the donation of an organ. Objective: To know the perceptions of people undergoing kidney transplantation about the organ donation. Methods: Descriptive and qualitative study, in which 20 people with renal transplantation participated. The analysis of the data followed the phases: ordering, classification of data and final analysis. Results: The data present the manifestation about the need of organ donation, being encouraged by media promotion, although only the family can take the option for donation when it comes with the death of a loved one, the question of the compatibility of the organ for the recipient, the effort to be able to realize the donation and to recommence the life. Conclusion: For the participants the donation of organs, especially the kidney, consists of a positive event in the life of the person which receives the renal graft. And with the realization of the dream of being transplanted, there is a rebirth to continue life.